2014
DOI: 10.1021/bm5006195
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Well-Defined Elastin-Like Polypeptide–Poly(ethylene glycol) Conjugates

Abstract: A series of stimulus-responsive elastin-like polypeptide-poly(ethylene glycol) (ELP-PEG) block copolymers was synthesized. The polymeric building blocks were conjugated via the efficient and specific strain-promoted alkyne-azide cycloaddition (SPAAC). For this purpose, ELP and PEG blocks were functionalized with azide and cyclooctyne moieties, respectively. Azides were introduced by applying a recently developed pH-controlled diazotransfer reaction on the primary amines present in ELP (N-terminus and lysine si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…Moreover, some functional groups can only be introduced by the use of unnatural amino acids, which in general significantly lower the production yields. 13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some functional groups can only be introduced by the use of unnatural amino acids, which in general significantly lower the production yields. 13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the present work was to improve the versatility of this post-synthesis ELP modification strategy to accommodate a wider range of side-chain functionality, while also being able to retain and tune polysulfonium ELP derivative thermoresponsive properties. 17 To accomplish this goal, we have redesigned ELP sequences to contain fewer Met residues, since the high charge density obtained when sulfonium ions were generated in every pentapeptide repeat in (VPGMG) 20 resulted in very hydrophilic polymers. Decreasing the density of functionalization sites was envisioned to help retain thermoresponsive properties, while also allowing reasonable levels of functional modification.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] PEGylation, the covalent attachment of polyethylene glycol, is a versatile means to increase a protein's size, stability and solubility. 2,[8][9][10][11] The increased radius of protein-PEG conjugates leads to a reduction in renal filtration, which together with decreased immunogenicity can result in longer circulation half lives compared to the native protein.…”
Section: Introductionmentioning
confidence: 99%
“…ELP liposomes displayed significantly better tumor localization at 6 and 12 hours after preheating; furthermore, these levels exceeded the concentration achieved for free drug by 31-fold. Additional hybridized systems, including PEG-functionalized ELPs[99], are also currently under investigation by several other groups.…”
Section: Applicationsmentioning
confidence: 99%